2022
DOI: 10.1016/j.procs.2021.12.051
|View full text |Cite
|
Sign up to set email alerts
|

A Micro-analysis Approach in Understanding Electronic Medical Record Usage in Rural Communities: Comparison of Frequency of Use on Performance Before and During the COVID-19 Pandemic

Abstract: In strengthening eHealth in the Philippines to support the universal health care (UHC) law, the scaling up and full adoption of electronic medical record (EMR) systems was strategically scheduled and supposedly completed in 2020. The Covid-19 pandemic, however, delayed these strengthening efforts. We wanted to assess the status of EMR adoption in primary clinics of rural health units (RHUs) and understand the frequency of use, particularly during the pandemic. Through analyses of EMR usage logs from selected R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Far back in 2005, the potential of employing information communication technology (ICT) systems has been recognized by the World Health Organization (WHO), in helping to transform health delivery systems and services positively, thereby urging member states to set up long-lasting strategies for the use of ICT in the health sector [9]. Consequently, with the current pandemic in place, the role played by information technology in health systems has been accelerated.…”
Section: ) Healthcare Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Far back in 2005, the potential of employing information communication technology (ICT) systems has been recognized by the World Health Organization (WHO), in helping to transform health delivery systems and services positively, thereby urging member states to set up long-lasting strategies for the use of ICT in the health sector [9]. Consequently, with the current pandemic in place, the role played by information technology in health systems has been accelerated.…”
Section: ) Healthcare Systemsmentioning
confidence: 99%
“…One such study examined the adoption as well as utilization of EMR technology in rural primary care settings. Their study revealed a non-parallel level of EMR utilization at primary care levels, thus instigating the need for a more granular approach to study adoption that can help in improving EMR usage quality, thereby contributing to the improvement of health service delivery and financing [9]. Similarly, in a qualitative descriptive study on the perception of nurses concerning the critical care work system during the COVID-19 pandemic [11], it was discovered that communication between patients and families was facilitated via iPad tablets supplied by respective organizations.…”
Section: ) Healthcare Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…It encompasses all sources of health data, including those related to health facilities and communities, electronic health records for patient care, populationbased data, information about human resources, finances, supply chains, and surveillance, as well as how that information is used and disseminated. [1]. Electronic health records (EHR), electronic medical records (EMR), health information exchange (HIE), computerized physicians order entry (CPOE), hospital information systems, and telemedicine/telehealth/e-health have all developed acronyms over time to describe electronic HISs [2] [3] [4] [5] [6].…”
Section: Introductionmentioning
confidence: 99%